Necropolitics - Mbembe, Achille, 1957- (Theory in forms., 2019)
"In Necropolitics Achille Mbembe, a leader in the new wave of francophone critical theory, theorizes the genealogy of the contemporary world, a world plagued by ever-increasing inequality, militarization, enmity, and terror as well as by a resurgence of racist, fascist, and nationalist forces determined to exclude and kill. He outlines how democracy has begun to embrace its dark side---what he calls its "nocturnal body"--Which is based on the desires, fears, affects, relations, and violence that drove colonialism. This shift has hollowed out democracy, thereby eroding the very values, rights, and freedoms liberal democracy routinely celebrates. As a result, war has become the sacrament of our times in a conception of sovereignty that operates by annihilating all those considered enemies of the state. Despite his dire diagnosis, Mbembe draws on post-Foucauldian debates on biopolitics, war, and race as well as Fanon's notion of care as a shared vulnerability to explore how new conceptions of the human that transcend humanism might come to pass. These new conceptions would allow us to encounter the Other not as a thing to exclude but as a person with whom to build a more just world."